2022
DOI: 10.2147/ijn.s378074
|View full text |Cite
|
Sign up to set email alerts
|

Nanotechnology: A Promising Approach for Cancer Diagnosis, Therapeutics and Theragnosis

Abstract: Cancer remains the most devastating disease and the major cause of mortality worldwide. Although early diagnosis and treatment are the key approach in fighting against cancer, the available conventional diagnostic and therapeutic methods are not efficient. Besides, ineffective cancer cell selectivity and toxicity of traditional chemotherapy remain the most significant challenge. These limitations entail the need for the development of both safe and effective cancer diagnosis and treatment options. Due to its r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
27
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 59 publications
(36 citation statements)
references
References 153 publications
0
27
0
Order By: Relevance
“…Theragnosis is an effective strategy for the management of specific diseases and combines diagnosis and therapy ( Lee et al, 2012 ; Ryu et al, 2012 ; Doan et al, 2021 ; Dessale et al, 2022 ). Generally, theragnosis requires non-invasive imaging methods, including fluorescence, photoacoustic imaging (PAI), positron emission tomography (PET), and MRI.…”
Section: Theragnosismentioning
confidence: 99%
“…Theragnosis is an effective strategy for the management of specific diseases and combines diagnosis and therapy ( Lee et al, 2012 ; Ryu et al, 2012 ; Doan et al, 2021 ; Dessale et al, 2022 ). Generally, theragnosis requires non-invasive imaging methods, including fluorescence, photoacoustic imaging (PAI), positron emission tomography (PET), and MRI.…”
Section: Theragnosismentioning
confidence: 99%
“…Nanotechnology has recently attracted significant attention worldwide for cancer treatment ( 92 ). Previous research revealed the gC1qR was the receptor for tumor-homing peptide LyP-1 which could specifically bind to tumor lymphatics and tumor cells ( 79 , 93 , 94 ).…”
Section: Potential For Translating Into Clinicmentioning
confidence: 99%
“…Nanomedicine has developed into a cutting-edge approach to cancer treatment and a captivating diagnostic tool. It is possible, to recent advancements in the usage of nanoparticles (NPs), to create a safe and very effective method of delivering anticancer drugs to the target tissues [13,14]. It has been established that the physicochemical characteristics of AuNPs, including the charge, size, and surface chemistry, affect their toxicity [15,16].…”
Section: Introductionmentioning
confidence: 99%